RNA in extracellular vesicles - Kim, Kyoung Mi; Abdelmohsen, Kotb; Mustapic, Maja; Kapogiannis, Dimitrios; Gorospe, Myriam (Wiley interdisciplinary reviews. RNA, 2017)
Cells release a range of membrane‐enclosed extracellular vesicles (EVs) into the environment. Among them, exosomes and microvesicles (collectively measuring 40–1000 nm in diameter) carry proteins, signaling lipids, and nucleic acids from donor cells to recipient cells, and thus have been proposed to serve as intercellular mediators of communication. EVs transport cellular materials in many physiologic processes, including differentiation, stem cell homeostasis, immune responses, and neuronal signaling. EVs are also increasingly recognized as having a direct role in pathologies such as cancer and neurodegeneration. Accordingly, EVs have been the focus of intense investigation as biomarkers of disease, prognostic indicators, and even therapeutic tools. Here, we review the classes of RNAs present in EVs, both coding RNAs (messenger RNAs) and noncoding RNAs (long noncoding RNAs, microRNAs, and circular RNAs). The rising attention to EV‐resident RNAs as biomarkers stems from the fact that RNAs can be detected at extremely low quantities using a number of methods. To illustrate the interest in EV biology, we discuss EV RNAs in cancer and neurodegeneration, two major age‐associated disease processes. WIREs RNA 2017, 8:e1413. doi: 10.1002/wrna.1413 This article is categorized under: RNA Export and Localization > RNA Localization Extracellular vesicles (EVs) contain different RNA species, including messenger RNAs (mRNAs), microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and Circular RNAs (cirRNAs). These cargo RNAs may affect gene expression patterns in recipient cells and/or serve as diagnostic and prognostic markers.